1981
DOI: 10.1083/jcb.91.2.524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytochalasin B on membrane-associated microfilaments in a cell-free system.

Abstract: The mode of action of cytochalasin B was examined in vitro using bile canaliculusenriched plasma membrane fractions isolated from rat liver. The pericanalicular microfilaments, which are mainly actin filaments and which are normally attached to the canalicular membranes, were dissociated from the membranes by cytochalasin B treatment. A microfilamentous network was found in the supernate of the cytochalasin-treated specimens and a number of polypeptides, of which a polypeptide corresponding in molecular weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…We first determined the optimal CB concentration and treatment time which could promote cells to release large number of vesicles, while having minimal cytotoxic effect. CB has been well-established as a metabolite which could promote cells to release large number of EVs from their surface by involving in cytoskeleton-membrane interaction [27]. These EVs have been exploited in a wide range of biomedical applications, as they are known to reflect the biological characteristics of the parental cells that they have been originated from [28].…”
Section: Resultsmentioning
confidence: 99%
“…We first determined the optimal CB concentration and treatment time which could promote cells to release large number of vesicles, while having minimal cytotoxic effect. CB has been well-established as a metabolite which could promote cells to release large number of EVs from their surface by involving in cytoskeleton-membrane interaction [27]. These EVs have been exploited in a wide range of biomedical applications, as they are known to reflect the biological characteristics of the parental cells that they have been originated from [28].…”
Section: Resultsmentioning
confidence: 99%
“…Using isolated hepatocyte couplets and time lapse microscopy, it has been shown that bile canaliculi repeatedly open and close and that this motion is accompanied by the expelling of a bolus of bile (52,55). We have interpreted this motility as active bile canalicular contractions (47,52,54,55,66), but others consider the motile events as noncontrac-tile collapses of canaliculi resulting from secretory pressure with rupture of canaliculi (9,11,30,35). In this report, we have taken advantage of the biliary secretion of sodium fluorescein by hepatocytes to visualize the bile canalicular system and have examined canalicular motility in the living state in order to shed light on these issues.…”
mentioning
confidence: 97%
“…Bile canalicular F-actin changes its volume in various liver cholestasis. In experimental animals, phalloidin and cytochalasin B treatments make bile canalicular F-actin either overpolymerized or depolymerized, respectively, to cause intracanalicular MV disappearance and intrahepatic jaundice (4,10,19,23). Abnormality of bile canalicular F-actin was frequently observed in patients and animals with obstructive jaundice, drug induced liver injury and other hepatic disorders (9,31).…”
mentioning
confidence: 99%